2015
DOI: 10.1007/s10120-015-0484-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features of gastric cancer in young patients

Abstract: Background Early-onset gastric cancer is relatively rare. To evaluate the clinicopathological features and surgical outcome of young patients with gastric cancer, this retrospective comparative study was conducted. Methods From 2000 to 2010, 4882 patients underwent surgery for gastric adenocarcinoma in our institution. A total of 136 patients under 40 years old were enrolled as the young group, and a total of 1435 patients aged between 60 and 69 were identified as the control group for this study. The patient'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
137
3
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(167 citation statements)
references
References 20 publications
14
137
3
13
Order By: Relevance
“…About half of the patients were diagnosed as SRC, and there were slight female predominance. Previous studies have reported young age GC shows slight female predominance or similar prevalence between both sexes, with higher rate of poorly differentiated carcinoma or SRC by pathologic review [4,5,14]. Previously mentioned clinical characteristics were in concordance to studies mentioned above.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…About half of the patients were diagnosed as SRC, and there were slight female predominance. Previous studies have reported young age GC shows slight female predominance or similar prevalence between both sexes, with higher rate of poorly differentiated carcinoma or SRC by pathologic review [4,5,14]. Previously mentioned clinical characteristics were in concordance to studies mentioned above.…”
Section: Discussionsupporting
confidence: 76%
“…In Western studies, the prevalence of AGCa is by far higher than EGCa [6,10]. Compared to Western, the prevalence of AGCa and EGCa were similar in Asian studies [4,5,14], alike to our analysis. This discrepancy may be due to different screening program between Western and Asia.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…It mainly occurred in older population, with a peak reported incidence for patients from 50 to 70 years. [5] However, the rate of GC in young patients has increased over the past few decades, despite a reduction in the overall prevalence of the disease. [6] Age at diagnosis, a key variable, not only was used as an indispensable adjusted element in the observational studies, but also contained inestimable value for prognosis.…”
Section: Introductionmentioning
confidence: 99%